Meteorosensitive architecture: Biomimetic building skins based on materially embedded and hygroscopically enabled responsiveness. (March 2015) - Reichert, Steffen; Menges, Achim; Correa, David
Abstract: In this paper, the authors present research into autonomously responsive architectural systems that adapt to environmental changes using hygroscopic material properties. Instead of using superimposed layers of singular purpose mechanisms–for sensing, actuation, control and power–in the form of high-tech electronic equipment as is emblematic for current approaches to climate responsiveness in architecture, the presented research follows an integrative, no-tech strategy that can be considered to follow biological rather than mechanical principles. In nature plants employ different systems to respond to environmental changes. One particularly promising way is hygroscopic actuation, as it allows for metabolically independent movement and thus provides an interesting model for autonomous, passive and materially embedded responsiveness. The paper presents a comprehensive overview of the parameters, variables and syntactic elements that enable the development of such meteorosensitive architectural systems based on the biomimetic transfer of the hygroscopic actuation of plant cones. It provides a summary of five years of research by the authors on architectural systems which utilize the hygroscopic qualities of wooden veneer as a naturally produced constituent within weather responsive composite systems, which is presented through an extensive analysis of research samples, prototypes at various scales, and two comprehensive case studies of full scale constructions. Highlights: Access and instrumentalisation of computational capacities within organic systems. Formal complexity through singular parametric differentiation in material behaviour. Environment cognisant architectural systems with climate dependent formal behaviour. Embedded biomimetic intelligence through material programming.